FACTORS ASSOCIATED WITH THE IMPL FACTORS ASSOCIATED WITH THE IMPLEMENTATION OF INTEGRATED MANAGEMENT OF SICK CHILDREN IN THE HEALTH CENTER - Susanti, Adrina (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2021)
In 2005 WHO, UNICEF, in collaboration with the Ministry of Health implemented an approach in early detection in toddlers, an MTBS program. Integrated Management of Sick Toddlers (MTBS) is an integrated approach in the management of sick toddlers and young infants with a focus on the health of children aged 0- 59 months comprehensively and efficiently. This study aims to determine the factors associated with the implementation of integrated management of sick children in the Health Center of Lhokseumawe City. The study was analytic with cross sectional design on March 1 - 14, 2020. The research subjects used a total population method, namely 114 staff of the Lhokseumawe City Health Center staff who provided basic health services who had attended MTBS training by using a questionnaire. Data were analyzed with Chi-Square test and multiple logistic regression. The results show there is the influence of knowledge (Ï-value = 0.001), motivation Ï-value = 0,000), the availability of tools (Ï-value = 0.075), and reward (Ï-value = 0,000). The results of multivariate analysis showed that the factor that most significantly influenced the MTBS implementation was the motivation factor with a value of Ï-value of 0,000. It is suggested that officers who have received training are expected to be required to hold training on the job training, with the aim of refresing and increasing the implementation of IMCI supervision by including technical guidance, on the management of IMCI activities in the puskesmas, and recording / reporting the implementation of the IMCI program by the City DINKES Lhokseumawe, so that the implementation of IMCI is in line with WHO and Ministry of Health expectations.